Deconstructing Post-WWII New York City : the Literature, Art, Jazz, and Architecture of an Emerging Global Capital. - Bennett, Robert (American popular history and culture (Routledge (Firm)), 2013)
Situating post-WWII New York literature within the material context of American urban history, this work analyzes how literary movements such as the Beat Generation, the New York poets and Black Arts Moment criticized the spatial restructuring of post-WWII New York City.